Response of fabric insert injection overmolding PP based composites subjected to single and muti-impact - José António Martins Ferreira; Tiago Febra; José Costa; Carlos Capela (Fracture and Structural Integrity)
This paper presents the results of a current study on the development and impact response of composite plates manufactured by injection overmolding on the two sides of a single reinforcement fibre mat. The injection polymer is a talc-filled polypropylene, nowadays used for structural purposes. Three configurations with different insert fibre mats were used: Kevlar, biaxial and multiaxial glass fibre mats. The parameters studied were the fibre mat type and the impact energy. For single impact tests, it was concluded that the highest impact energy required to achieve impactor perforation is obtained with Kevlar insert, while the highest percentage of energy recovered is achieved with biaxial glass fibre netting. Kevlar insert also allows for the maximum impact stiffness. For the multi-impact tests, the recovered energy and the dynamic stiffness show the same tendencies of the single impact tests. On low energy impacts, the effect of the insert fibre and of the previous impact are quite reduced, while for impact energies above 6J, previous impacts reduce significantly the recovered energy and the impact energy for which the perforation was achieved.